Specific targeting of antiapoptotic Bcl-2 proteins as a radiosensitizing approach in solid tumors - Sobol, Benjamin; Azzam Nieto, Osama; Eberlein, Emily Lara; Scherr, Anna-Lena; Ismail, Lars; Keßler, Annika; Nader, Luisa; Schwab, Maximilian; Hoffmeister-Wittmann, Paula; Schmitt, Nathalie; Jäger, Dirk; Welte, Stefan Ezechiel; et al. (International journal of molecular sciences, 2022)
Avoidance of therapy-induced apoptosis is a hallmark of acquired resistance towards radiotherapy. Thus, breaking resistance still challenges modern cancer therapy. The Bcl-2 protein family is known for its regulatory role in apoptosis signaling, making Bcl-2, Mcl-1 and Bcl-xL promising targets. This study evaluates the effects of highly specific inhibitors for Bcl-xL (WEHI-539), Bcl-2 (ABT-199) and Mcl-1 (S63845) as radiosensitizers. Covering a broad spectrum of solid tumors, Non-Small-Cell Lung Cancer (NSCLC), Head and Neck Squamous Cell Carcinoma (HNSCC) and synovial sarcoma cell lines were exposed to fractionated radiation as standard therapy with or without Bcl-2 protein inhibition. Protein expression was detected by Western blot and cell death was assessed by flow cytometry measuring apoptosis. In contrast to NSCLC, a high level of Bcl-xL and its upregulation during radiotherapy indicated radioresistance in HNSCC and synovial sarcoma. Radioresistant cell lines across all entities benefited synergistically from combined therapy with Bcl-xL inhibition and fractionated radiation. In NSCLC cell lines, Mcl-1 inhibition significantly augmented radiotherapy independent of the expression level. Our data suggest that among antiapoptotic Bcl-2 proteins, targeting Bcl-xL may break resistance to radiation in HNSCC, synovial sarcoma and NSCLC in vitro. In NSCLC, Mcl-1 might be a promising target that needs further investigation.
Gesehen am 19.08.2022